2018
DOI: 10.1111/eos.12402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of finish line design on stress distribution in bilayer and monolithic zirconia crowns: a three‐dimensional finite element analysis study

Abstract: This study evaluated the influence of different finish line designs and abutment materials on the stress distribution of bilayer and monolithic zirconia crowns using three-dimensional finite element analysis (FEA). Three-dimensional models of two types of zirconia premolars - a yttria-stabilized zirconia framework with veneering ceramic and a monolithic zirconia ceramic - were used in the analysis. Cylindrical models with the finish line design of the crown abutments were prepared with three types of margin cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
2
12
0
6
Order By: Relevance
“…The finding that the chamfer design crowns fractured at a higher load than did the slice design crowns in both production‐method groups indicates that the commonly recommended chamfer margin design gives the strongest crowns. This is in accordance with previous studies . The increased thickness in the crown margin probably explains this result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding that the chamfer design crowns fractured at a higher load than did the slice design crowns in both production‐method groups indicates that the commonly recommended chamfer margin design gives the strongest crowns. This is in accordance with previous studies . The increased thickness in the crown margin probably explains this result.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reveal that alterations in margins design affect the cervical stress distribution . The lowest load at fracture was 1,202 N, which is higher than the maximally measured biting force of 800–1,000 N .…”
Section: Discussionmentioning
confidence: 81%
“…We found that monolithic traditional zirconia with shoulder margin design has higher fracture load than monolithic traditional zirconia with feather-edge margin design in both groups. It might be because the stress distribution pattern in the shoulder margin design as the circumferential shoulder withstands occlusal forces and results in less concentration of stress on axial walls 2627. Furthermore, an increase in the crown margin and axial wall thickness lead to fracture at a higher load.…”
Section: Discussionmentioning
confidence: 99%
“…Miura ve ark. 23 shoulder, rounded shoulder ve derin chamfer basamak tiplerini Sonlu Elemanlar Stres Analiz yöntemi ile karşılaştırmışlar, derin chamfer ve rounded shoulder basamak tipinin zirkonyum restorasyonların mekanik performanslarını geliştirdiğini gözlemlemişlerdir. Malament ve Socransky 24 shoulder ve chamfer basamak şekillerinin tam seramiklerde vener porselenlerin kırılma riski açısından önemli bir fark oluşturmadığını belirtmişlerdir.…”
Section: Discussionunclassified